Short Communication: New record of Stenotrophomonas sp. as endosymbiont bacteria in Rhizopus microsporus - Dewi Peti Virgianti; Desi Natalia; I Nyoman Pugeg Aryantha (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Virgianti DP, Natalia D, Aryantha INP. 2020. Short Communication: New record of Stenotrophomonas sp. as endosymbiont bacteria in Rhizopus microsporus. Biodiversitas 21: 1678-1685. Rhizopus sp. are closely related to humankind in many aspects of human life. Several species of Rhizopus are important in food, agriculture, and health industries. Rhizopus microsporus has endosymbiont bacteria that has been identified as Burkholderia sp. This study aimed to identify the endosymbiont bacteria in R. microsporus isolated from Moringa oleifera Lam leaves. Ring technique, simple method of agar heap technique and antibiotic technique, was conducted to purify the hyphae and to eliminate ectosymbiont and contaminant bacteria outside the hyphae. The presence of endosymbiont bacteria in R. microsporus was determined by using LIVE/DEAD® BacLight Bacterial Viability Kits L13152 and the Fluorescent in Situ Hybridization (FISH) method using EUB338 probes. It was suggested that the culturable endosymbiont bacteria was identified as Stenotrophomonas sp. based on the phylogenetic tree using the 16S rDNA